Bank Capital, Securitization and Credit Risk: An Empirical Evidence - Dionne, Georges; Harchaoui, Tarek M. (Assurances et gestion des risques / Insurance and Risk Management, 2008)
This paper is one of the first attempts to conduct an empirical investigation of the relationship between bank capital, securitization and bank risk-taking in a context of the rapid growth in off-balance-sheet activities. The data come from the Canadian financial sector. Evidence from the 1988-1998 period indicates that: (a) securitization has a negative statistical link with both current Tier 1 and Total risk-based capital ratios, and (b) there exists a positive statistical link between securitization and bank risk-taking. Profit-risk measure is more sensitive than loss-risk measure to the variation in securitization activity. These results seem to agree, during the studied period, with models indicating that banks might be induced to shift to more risky assets under the current capital requirements for credit risk because the regulatory capital levels are considered too high.